The Effects of New Franchisor Partnering Strategies on Franchise System Size - Shane, Scott; Shankar, Venkatesh; Aravindakshan, Ashwin (Management Science, 2006)
Many young firms use strategic actions to attract partners who help them increase the size of their operations quickly. This article examines the use of strategic actions to attract partners and increase system size in the context of franchising. We build on research in entrepreneurship, marketing, organization theory, strategic management, and finance to develop specific hypotheses about the influences of franchisor pricing policy and strategic control decisions on system size. We test these hypotheses empirically, using panel data on a sample of 1,292 business format franchise systems from 152 industries that were established in the United States between 1979 and 1996 and followed from their inception forward in time. Our model accounts for the endogeneity of strategic decisions, controls for unobserved firm and industry factors, and accounts for selection effects due to system failure. The results show that franchisors that grow larger (1) lower royalty rates as the systems age, (2) have low up-front franchise fees that rise over time, (3) own a small proportion of outlets and lower that percentage over time, (4) keep franchisees’ initial investment low, and (5) finance their franchisees.